Numerical Simulation of Splitting Devices in Horizontal Pipeline - Mat Isa, N.; Ab Rahman, A. F.; Sadikin, A. (Journal of Advanced Research in Applied Mechanics, 2020)
This research was carried out to determine the suitable splitting device for horizontal pipeline in a pulverised coal power plant. In this research, six splitting devices have been designed and only one device achieves the main objective which is to improve fluid flow to be a homogeneous flow in the pipe. The procedure of choosing the best device is from the velocity profile of the fluid after moving through the splitting device. From the data, ‘standard k-epsilon’ is the best method for the simulation of this research. The geometry of the device in this research is followed as the geometry used by another researcher for analysis through experimental approach. All analysis in this research is using software ANSYS 15.0.